The Effect Of Instructional Strategies And Vocabulary Mastery On English Writing Skill - Yanti Sofiyanti; Moch. Sukardjo; Etin Solihatin (STAI Miftahul Ula Nganjuk, 2024)
The purpose of this study is to know the effect of instructional strategies and vocabulary mastery on English writing skill. This study is a quantitative one.The research design is 2x2 treatment by level which consist of instructional strategies (A) and vocabulary mastery (B). Instructional strategies (A) consist of groups that are treated by collaborative writing strategy (A1) as an experimental class, and cooperative integrated reading and composition strategy (A2) as a control class. While vocabulary mastery (B) consists of two groups, they are the high vocabulary mastery group (B1) and the low vocabulary mastery group (B2). Based on the result of the research, it is shown that the mean score of collaborative writing is higher than the mean score of cooperative integrated reading and composition. Significance (Sig.) .002 <0.005 which indicates that the variable has an interaction, the instructional strategies and vocabulary mastery have a significant effect on English writing skill. It can be concluded that instructional strategies and vocabulary mastery can promote English writing skill